Industrial data ecosystems and data spaces - Frederik Möller; Ilka Jussen; Virginia Springer; Anna Gieß; Julia Christina Schweihoff; Joshua Gelhaar; Tobias Guggenberger; Boris Otto (Electronic Markets, 2024)
Abstract Industrial data ecosystems are inter-organizational forms of cooperation emerging around sharing data. They arise from a digital infrastructure, giving data providers and data users a platform to share and (re-)use data. Data spaces are among the digital infrastructures frequently associated with data ecosystems, as they supply a shared digital space for its participants to share data in a sovereign way. Data spaces aim to close a gap in the digital infrastructure landscape, addressing concerns of organizations when sharing data, such as data misappropriation or a lack of control of shared data. They do this by implementing data sovereignty—typically through Usage Control Policies—that give data providers the means to formalize semantically and technically how data users are allowed to use their data. In this fundamentals article, we address the following issues: (1) contextualizing and demarcating data spaces and data ecosystems, (2) systematizing data spaces in the research and policy landscape, and (3) elaborating on a research agenda for Information Systems (IS) research.
Additional information: A1
Keywords: 330; Data ecosystems; Data sharing; Data spaces